THE IMPROVEMENT OF STUDENT LEARNING OUTCOMES IN IPS LEARNING WITH COOPERATIVE TYPE STAD MODEL - GUSHERMIANDA, EZI; Nasrul, Nasrul; Zaiyasni, Zaiyasni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
Abstract The purpose of this study was to describe the improvement of student learning outcomes in social studies learning by using Cooperative Laerning Model Type STAD in class V SDN 04 Sungai Naning. The type of research used is Classroom Action Research using qualitative and quantitative approaches. The subjects of this study were 20 grade V students at SDN 04 Sungai Naning. The results showed an increase in terms of a) RPP in cycle I was 74.99% and cycle II was 92.85%, b) Implementation in the aspect of teachers in cycle I was 76.78% and cycle II was 92.85% while the implementation of aspects of students cycle I was 76.78% and cycle II was 92.85%, c) Student learning outcomes in cycle I were 79.84% and cycle II was 89.70%. Thus, the Cooperative Learning Type STAD model can improve student learning outcomes in social studies learning in class V SDN 04 Sungai Naning Keywords: IPS, STAD Cooperative Type Model.